Who Benefitted from the Peace Dividend in the DRC? - Marivoet, Wim; De Herdt, Tom; Ulimwengu, John M. (2019)
The first decade of the 21st century marked a new beginning for the Democratic Republic of the Congo (DRC). After the signing of a peace treaty in 2002, the country re-connected with the world to engage in post-conflict reconstruction. In this blogpost, the authors ask who really benefitted from the ensuing peace dividend? By re-examining the evidence, they conclude that the country missed an important opportunity to combat the country’s devastating poverty.